Production of hydroxyl radical by human alveolar macrophages. - Hoidal, J R (1979)
Stimulated human alveolar macrophages were demonstrated to oxidize B-methyl proprionaldehyde (methional) or 2-keto-4-thiomethylbutyric acid to ethylene (C2H4). Agents which are believed to scavenge the hydroxyl radical (.OH), sodium benzoate, and mannitol, as well as scavengers of superoxide anion (O2-) or hydrogen peroxide, decreased C2H4 production, implicaing .OH as the oxidizing radical. Differences in C2H4 rpoduction, as well as oxygen uptake and O2- release between human alveolar macrophages and polymorphonuclear leukocytes, were also documented.